Farmers’ Preferences for Varietal Traits, Their Knowledge and Perceptions in Traditional Management of Drought Constraints in Rice Cropping in Benin: Implications for Rice Breeding - ADOUKONOU-SAGBADJA, Hubert (My University, 2020)
Rice (Oryza spp.) is one of the most important crops that significantly contribute to food security in Benin. In the current context of climate change, drought is known to be the main abiotic stress in crops and a major yield-limiting factor for agricultural production worldwide. To assess farmers’ knowledge, the preference traits of the rice cultivars in use, their perceptions and management of drought stress in rice production in Benin, an ethnobotanical investigation was conducted in 50 villages throughout the major zones. The results showed that High yield combined with good grain quality (including good taste, softness after cooking, less starch, white pericarp, long grain length and swelling when cooked), medium maturing and tolerance to drought and flood were the most desired traits motivating farmers for growing rice cultivars. Taste and high yield were the paramount traits of IR841, the most popular rice variety currently cropped in Benin followed by its fragrance. Drought constraints was reported as the most damaging abiotic stress across the villages surveyed with field lost estimated up to 100% at the flowering stage. Changing sowing date (80%), the use of irrigation systems (10%) and the cropping of early maturing cultivars (7%) were the most traditional strategies to reduce drought impacts. Needs for tolerant varieties were clearly expressed by farmers to mitigate drought effects on rice production in Benin. The results of this survey emphasize the need for rice breeders to focus more on improving grain quality in addition to high yield potential and tolerance to abiotic stresses mainly drought.
Keywords: Benin; drought constraints; farmers’ perceptions; preferences; rice cropping